lncRNA-MIAT rs9625066 polymorphism could be a potential biomarker for ischemic stroke - Yin-Hua Weng; Jie Chen; Wen-Tao Yu; Yan-Ping Luo; Chao Liu; Jun Yang; Hong-Bo Liu (BMC, 2024)
Abstract Background Ischemic stroke (IS) is a common and serious neurological condition that is highly fatal but so far no early diagnostic markers are available. Myocardial infarction-associated transcript (MIAT) is a long non-coding RNA (lncRNA) that could lead to IS by inducing autophagy and apoptosis in neuronal cells. However, there has been no report on the link between susceptibility to IS and the single-nucleotide polymorphisms (SNPs) of MIAT. This study aimed to investigate the association between MIAT gene polymorphisms and IS risk. Methods A total of 320 IS patients and 310 age-, sex- and race-matched controls were included in this study. Four polymorphisms (rs2157598, rs5761664, rs1894720, and rs9625066) were genotyped by using SNPscan technique. Results Among the 4 polymorphisms of MIAT, only rs9625066 was associated with IS risk (CA vs. CC: adjusted OR = 0.55, 95% CI, 0.37-0.85, P = 0.006; AA vs. CC: adjusted OR = 0.39, 95% CI, 0.16-0.94, P = 0.036; (AA + CA vs. CC: adjusted OR = 0.53, 95% CI, 0.35-0.80, P = 0.002; A vs. C adjusted OR = 0.59, 95% CI, 0.42-0.82, P = 0.002). Haplotype analysis showed a 1.32-fold increase (95% CI, 1.05-1.67, P = 0.017) in IS risk for rs2157598-rs5761664-rs1894720-rs9625066 (A-C-G-C). Logistic regression analysis identified some independent impact factors for IS including rs9625066 AA/AC, TC, TG, HDL-C (P < 0.05). Conclusion The rs9625066 polymorphism of MIAT might be associated with IS susceptibility in Chinese population, in which AA/CA plays a protective role in IS, whereas the CC genotype increases the risk of developing IS, suggesting it might be a marker predictive of IS risk.